Pengaruh Digital Product Management Terhadap Pengembangan Aplikasi Go-Jek - Mohammad Abhinaya Ramadhan; Yuniningsih Yuniningsih (International Forum of Researchers and Lecturers, 2024)
This research focuses on qualitative analysis regarding the influence of Digital Product Management (DPM) on Gojek application development. Gojek, as an application-based service platform, relies on DPM to effectively manage and develop their digital products. This research approach involved in-depth interviews with product development team members at Gojek and content analysis of DPM-related documents. The analysis results show that DPM plays a crucial role in shaping the direction and quality of Gojek application development. Key findings include DPM's success in designing product strategies focused on customer needs and ongoing market trends. Flexible management of changing customer and overall market needs was also found to be a key element in DPM effectiveness. In addition, synergy between the DPM team and the technical development team is the key to success, where effective communication and a deep understanding of the product's goals play a crucial role. Organizational factors such as collaborative culture and flexibility in decision making also influence the influence of DPM on application development. This research provides in-depth qualitative insight into how DPM can influence application development in the Gojek context. The practical implications can help similar companies to understand the importance of qualitative factors in managing their digital products and build strategies that are more adaptive to market changes. Additionally, these findings provide a basis for companies to improve collaboration between DPM teams and technical development teams to increase the success of application development in the future.